Cardiotoxicity of novel HER2-targeted therapies. (7th June 2013) - Sendur, Mehmet A.N.; Aksoy, Sercan; Altundag, Kadri
Abstract: Background: Trastuzumab, an anti-HER2 humanized monoclonal antibody, is the standard treatment for both early and metastatic HER2-positive breast cancer. In addition to other chemotherapeutic agents, trastuzumab significantly improves response rate and survival in HER2-positive early and metastatic breast cancer. Although it is well known that trastuzumab therapy is closely associated with both symptomatic and asymptomatic cardiotoxicity, less is known about novel HER2-targeted therapies. The aim of this review is to discuss the cardiac safety data from recent studies of novel anti-HER2 drugs other than trastuzumab. Scope: Novel HER2-targeted therapies showed favorable results in HER2 positive metastatic breast cancer patients. Pubmed database, ASCO and San Antonio Breast Cancer Symposium Meeting abstracts were searched until January 2013 using the following search keywords; 'trastuzumab, trastuzumab cardiotoxicity, HER-2 targeted therapies, lapatinib, pertuzumab, trastuzumab emtansine, afatinib and neratinib'; papers which were considered relevant for the aim of this review were selected by the authors. Lapatinib, pertuzumab, T-DM1, neratinib and afatinib molecules are evaluated in the study. Findings: In a comprehensive analysis, 3689 lapatinib treated patients enrolled in 49 trials; asymptomatic cardiac events were reported in 53 patients (1.4%) and symptomatic grade III and IV systolic dysfunction was observed only in 7 patients (0.2%) treated with lapatinib. In phase I–III trials of pertuzumab, cardiac dysfunction was seen in 4.5–14.5% of patients with pertuzumab treatment and cardiac dysfunction was usually grade I and II. Cardiotoxicity of pertuzumab was usually reported with the trastuzumab combination and no additive cardiotoxicity was reported with addition of pertuzumab to trastuzumab. T-DM1 had a better safety profile compared to trastuzumab, no significant cardiotoxicity was observed with T-DM1 in heavily pre-treated patients. In the EMILIA study, only in 1.7% of patients in the T-DM1 group experienced reduction of left ventricular ejection fraction (LVEF) and grade III LVEF reduction developed only in one patient (0.2%) in the T-DM1 group compared to the lapatinib plus capacitabine group. In phase I–II trials with neratinib no cardiotoxicity was reported whereas cardiotoxicity was seen between 0–5.3% with afatinib treatment. Conclusion: Although cardiac toxicity has been reported as an adverse event for novel HER2-targeted therapies, cardiac dysfunction rate of the novel HER2-targeted therapies is significantly lower than the trastuzumab and combination of these agents with trastuzumab did not significantly increase the cardiac adverse events.